PEMBUATAN PROTOTIPE ALAT PENCUCIAN BATUBARA DENGAN METODE FLOTASI - Tito Alfredo; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Coal washing can be done by various methods. One method of washing that is quite easy to do is by flotation method. Coal washing is usually done in large companies with tools that tend to be large and costly. In the mining laboratory of Universitas Negeri Padang there is no coal leaching tool using flotation method. It is expected that with the manufacture of this tool can be a reference for the practice of washing coal with flotation methods in the mining lab of Universitas Negeri Padang.The tool functions normally and the coal sample has undergone a washing process so that a froth arises indicating the coal has been washed because it is lifted with froth. From the performance of the tool and the results obtained from the sample before and experienced washing where there was a reduction in sulfur levels in the sample from 0.378 % Adb decreased after washing to 0.235%Adb. There was a decrease in sulfur content of 0.143 %Adb. From the performance of the tool and the results obtained from the sample before and experienced washing where there was an increase in caloric value Data sample value of coal calories before washing obtained by 7689.87 Kcal / g, after washing there was an increase in caloric value to 8414.30 Kcal/g. there was an increase in caloric value of 724.43 Kcal/g. Keywords: flotation, washing, prototype, tools, coa